Halogen-free flame-retardant PPE / PA alloy and preparation method and application thereof

By using zinc borate or its composite flame retardant and maleic anhydride grafting toughener in PPE/PA alloy, it is solved that in the prior art, PPE/PA alloy cannot achieve halogen-free, high temperature and high humidity resistance and low simultaneously. Due to the precipitation problem, halogen-free flame-retardant PPE/PA alloys that meet the high performance requirements of photovoltaic connector materials were prepared.

CN119463487AActive Publication Date: 2025-02-18KINGFA SCI & TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411528180.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-18
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

The existing flame retardant system of PPE/PA alloys cannot achieve the requirements of halogen-free, high temperature and high humidity resistance and low precipitation at the same time, and cannot meet the high performance needs of photovoltaic connector materials.

Method used

Using zinc borate or its composite flame retardant as halogen-free flame retardant, combined with maleic anhydride grafting toughener, halogen-free flame retardant and 0-level CTI are prepared through specific PPE/PA alloy ratios and process conditions. , low precipitation and dimensional stability PPE/PA alloy.

Benefits of technology

V0 flame retardant is achieved, avoiding the whitening defects of the precipitation surface of conventional halogen-free flame retardants, and meeting the requirements of low precipitation and dimensional stability of photovoltaic connector materials at high temperature and high humidity.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a halogen-free flame-retardant PPE / PA alloy which comprises the following components in parts by weight: polyphenyl ether, polyamide, a halogen-free flame retardant and a toughening agent, wherein the halogen-free flame retardant is selected from at least one of zinc borate, a zinc borate / phosphazene compound and a zinc borate / antimony white compound; wherein the weight ratio of the polyphenyl ether to the polyamide is 1: (1-3.5); the flexibilizer is selected from any one or more of a maleic anhydride grafted styrene block copolymer and a maleic anhydride grafted ethylene-octylene copolymer. According to the halogen-free flame-retardant PPE / PA alloy, the 0-grade CTI effect can be achieved through the specific polyphenyl ether and polyamide compounding ratio, the size stability is good, the flame retardant achieves halogen-free flame retardance without precipitation, and the flexibilizer improves the low-temperature falling ball performance, so that the PPE / PA alloy has the advantages of being halogen-free, flame-retardant, 0-grade CTI, small in precipitation under high temperature and high humidity, capable of meeting the low-temperature falling ball standard of UL, good in size stability and high in mechanical property. Therefore, the PPE / PA alloy disclosed by the invention is suitable for a photovoltaic connector.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polymer technology, and in particular to a halogen-free flame-retardant PPE / PA alloy and a preparation method and application thereof. Background Art

[0002] As an amorphous engineering plastic, polyphenylene ether (PPE) has excellent flame retardancy, acid and alkali resistance, high temperature resistance, moisture and heat resistance, and dimensional stability. However, due to the viscosity and internal stress of PPE, it is more likely to suffer from stress cracking when in contact with oil. This limits its use in some applications with high stress resistance requirements and complex working conditions. By adding PA to PPE and taking advantage of the excellent solvent resistance, toughness, and fluidity of nylon, the prepared PPE / PA alloy can greatly improve the stress cracking resistance of PPE, thereby greatly expanding the application range of PPE materials.

[0003] Photovoltaic connectors are key parts that connect components, junction boxes, controllers, inverters, and other components in photovoltaic power generation systems. They have high material performance requirements. The key performance indicators of the materials are: halogen-free flame retardant, 0-level CTI, less material precipitation under high temperature and high humidity, reducing metal corrosion in the connector, and meeting UL's low-temperature drop ball standard: 51mm diameter, 535g weight steel ball*1.295m, -35℃ / 3h (UL).

[0004] However, the flame retardant systems used in PPE / PA alloys in the prior art cannot simultaneously achieve the requirements of halogen-free and resistant to precipitation. For example, patent CN103865256B discloses a method for preparing flame-retardant PPE / PA, which uses a flame retardant solution of melamine and red phosphorus, but such flame retardants are prone to precipitation under high temperature and high humidity conditions, and cannot meet the requirements of low precipitation of photovoltaic connector materials. For example, patent EP0448221B1 also discloses a method for preparing flame-retardant PPE / PA alloys, which uses a solution of nylon and brominated styrene, but cannot meet the halogen-free requirements of photovoltaic connectors. Summary of the invention

[0005] The object of the present invention is to overcome the above technical defects and provide a PPE / PA alloy which is halogen-free flame retardant, has a CTI of level 0, has little precipitation under high temperature and high humidity, meets the low temperature ball drop standard of UL, and has good dimensional stability.

[0006] The present invention is achieved through the following technical solutions: A halogen-free flame-retardant PPE / PA alloy, comprising the following components in parts by weight: Polyphenylene ether and polyamide 60-100 parts; 9-15 parts of halogen-free flame retardant; 3-12 parts of toughening agent; The halogen-free flame retardant is selected from at least one of zinc borate, zinc borate / phosphazene compound flame retardant, and zinc borate / antimony white compound flame retardant, wherein the weight ratio of zinc borate / phosphazene is (8-2):1, and the compounding ratio of zinc borate / antimony white is (8:2):1; Wherein, the weight ratio of polyphenylene ether to polyamide is in the range of 1:(1-3.5); The toughening agent is selected from any one or more of maleic anhydride grafted styrene block copolymers and maleic anhydride grafted ethylene-octene copolymers, wherein the grafting rate of maleic anhydride is 0.2-1wt%.

[0007] The content of zinc borate in the halogen-free flame-retardant PPE / PA alloy of the present invention is in the range of 6-13.3 parts.

[0008] The content of polyphenylene ether in the halogen-free flame-retardant PPE / PA alloy of the present invention is in the range of 13.3-50 parts.

[0009] The polyphenylene ether of the present invention is polymerized from 2,6-dimethylphenol or its derivatives. The intrinsic viscosity of the polyphenylene ether of the present invention measured in chloroform at 25°C using an Ubbelohde viscometer is in the range of 25-60 m 3 / g, preferably with an intrinsic viscosity of 35-45m 3 / g.

[0010] The polyamide is selected from at least one of aliphatic polyamide and semi-aromatic polyamide. The aliphatic polyamide resin is selected from PA66, PA46, PA610, PA612, PA56, PA510, PA512, PA910, PA912, PA913, PA914, PA915, PA616, PA936, PA1010, PA1012, PA1013, PA1014, PA1210, PA1212, PA1213, PA1214, PA614, PA613, PA615, PA616, etc.

[0011] The semi-aromatic polyamide is selected from PA MXD6, PA10T, PA10T1010, PA10T66, PA6T, PA6T66, PA9T, etc. Preferably, the halogen-free flame retardant contains only zinc borate and does not include other flame retardants.

[0012] The technical solution of the present invention has no particular limitation on the average particle size of zinc borate, phosphazene and antimony white. The purpose of the present invention can be achieved when the average particle size is within the range of 0.1 to 10 μm. The average particle size is measured by a particle size analyzer.

[0013] The phosphazene is selected from hexaphenoxy cyclotriphosphazene, phenoxy polyphosphazene and derivatives thereof. Preferably, the phosphazene is selected from hexaphenoxy cyclotriphosphazene. Specifically, the phenoxy polyphosphazene can be polydiphenoxy phosphazene.

[0014] Preferably, the grafting rate of maleic anhydride in the toughening agent is 0.4-0.7wt%.

[0015] The toughening agent of the present invention can be a commercially available product or can be obtained by self-production. The self-production method can be: the ungrafted toughening agent, maleic anhydride and initiator are subjected to grafting reaction through a twin-screw extruder (the screw temperature is 150-180°C and the aspect ratio is greater than or equal to 40:1), the initiator is selected from at least one of diisopropylbenzene peroxide, di-tert-butyl peroxide, tert-butyl hydroperoxide and isopropylbenzene hydroperoxide, and the amount of the initiator added is 0.2-0.8wt% of the total feed amount.

[0016] The test method for the grafting rate of maleic anhydride is titration. The specific operation method is: put the grafted material into xylene and heat it under reflux to dissolve. After cooling, add a certain amount of 0.05mol / L potassium hydroxide-ethanol solution, and then heat it under reflux for 8h. Use 0.1% phenolphthalein solution as an indicator and titrate it with 0.05mol / L HCl-isopropanol solution to the end point while it is hot. The grafting rate G is calculated by the following formula: G = (N1 × Vl - N2 × V2) × M ÷ w ÷ 10 Where: N1: KOH-ethanol solution equivalent concentration, N; V1: volume of KOH-ethanol solution, ml; N2: HCl-isopropanol solution equivalent concentration, N; V2: volume of HCl-isopropanol solution, ml; M: equivalent mass of maleic anhydride, g; w: weight of the dried sample after extraction, g.

[0017] The maleic anhydride grafted styrene block copolymer is selected from at least one of maleic anhydride grafted styrene-butadiene-styrene block copolymer, maleic anhydride grafted styrene-ethylene / butylene-styrene block copolymer and maleic anhydride grafted styrene-ethylene / propylene-styrene block copolymer.

[0018] In the PPE / PA alloy of the present invention, the toughening agent accounts for 5-12wt% of the total weight of the PPE / PA alloy.

[0019] The invention also comprises 0.1-2 parts of antioxidant by weight, wherein the antioxidant is selected from at least one of phenolic antioxidant, phosphite antioxidant or metal passivator.

[0020] The preparation method of the halogen-free flame-retardant PPE / PA alloy comprises the following steps: uniformly mixing the components according to the proportion, extruding and granulating through a twin-screw extruder, the screw speed is 250-500rpm; the extrusion temperature is 230-290°C, and the halogen-free flame-retardant PPE / PA alloy is obtained.

[0021] Application of halogen-free flame-retardant PPE / PA alloy for the preparation of photovoltaic connectors.

[0022] The present invention has the following beneficial effects: The present invention uses pure zinc borate or a zinc borate-based flame retardant under the premise of a specific PPE / PA alloy ratio, and can achieve V0 flame retardancy, effectively avoiding the defect of whitening of the surface of the conventional halogen-free flame retardant. At the same time, the ratio of the PPE / PA alloy of the present invention enables the material to achieve the effect of 0-level CTI while having good dimensional stability. In addition, the toughening agent grafted with maleic anhydride improves the compatibility of the resin matrix, and further enhances the toughness of the material to meet the low-temperature ball drop performance of the material at different temperatures. The prepared non-reinforced halogen-free flame-retardant PPE / PA alloy composition is very suitable for use in the field of photovoltaic new energy. DETAILED DESCRIPTION

[0023] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0024] The sources of raw materials used in the present invention are as follows: PPE: PPE LXR040, Bluestar, intrinsic viscosity 39.5-41.5 cm 3 / g; PA66: PA66 U3600 NC01, NVIDIA; PA612: PA612 A170, Shandong Guangyin New Materials; PA6T / 66: KFHP4, Zhuhai Wantong; Zinc borate: ZB-503, Yishitong; Hexaphenoxycyclotriphosphazene: HPCTP, Hongda Dante Chemical; Phenoxy polyphosphazene: Hubei Dali Chemical Co., Ltd. Antimony white: S-05N, Changde Chenzhou Antimony Products Co., Ltd.

[0025] Aluminum diethylphosphinate: OP 1230, Clariant; Toughening agent A-1: ​​SEBS grafted with maleic anhydride, maleic anhydride grafting rate is 0.2wt%, homemade; Toughening agent A-2: SEBS grafted with maleic anhydride, maleic anhydride grafting rate of 0.4wt%, homemade; Toughening agent A-3: maleic anhydride grafted SEBS, maleic anhydride grafting rate is 0.7wt%, homemade; Toughening agent A-4: maleic anhydride grafted SEBS, maleic anhydride grafting rate is 1wt%, homemade; Toughening agent A-5: maleic anhydride grafted SEBS, maleic anhydride grafting rate is 1.5wt%, homemade; Toughener B: maleic anhydride grafted ethylene-octene copolymer, maleic anhydride grafting rate is 0.6wt%, homemade; The homemade method of the maleic anhydride grafted toughening agent is as follows: the ungrafted toughening agent, maleic anhydride and initiator are subjected to grafting reaction through a twin-screw extruder (screw temperature is 150-180°C, aspect ratio is 44:1), the initiator is selected from dicumyl peroxide, and the amount of initiator added is 0.5wt% of the total feed amount. Among them, SEBS is purchased from SEBS 6151 of Formosa Plastics; POE is purchased from POE ENGAGE 8137 of DOW.

[0026] Toughening agent C: GMA grafted POE; SOG-02, Jiayirong; Toughener D: SEBS, SEBS 6151, Formosa Plastics; Toughener E: POE, POE ENGAGE 8137, DOW; Antioxidant: Antioxidant 1010 and antioxidant 168 are compounded in a weight ratio of 1:2.

[0027] Embodiment and comparative example PPE / PA alloy preparation method: according to the ratio, the components are mixed evenly, and granulated by extrusion through a twin-screw extruder, the screw speed is 400rpm; the temperature of each section of the barrel is set to 230°C, 250°C, 260°C, and 270°C to obtain a halogen-free flame-retardant PPE / PA alloy.

[0028] Various test methods: (1) Flame retardancy: According to UL94-2022 standard, 1.5 mm standard specimens were prepared and the vertical burning grade of the material was tested.

[0029] (2) Low-temperature drop ball performance: Referring to the UL standard, the sample was injection molded into a 100*100*1.5mm square plate. After conditioning at -35℃ for 3h, a steel ball with a diameter of 51mm and a weight of 535g was used to drop the ball at a distance of 1.295m to observe whether the square plate cracks. If cracked, it is NG, and if not cracked, it is OK.

[0030] (3) CTI: According to the CTI test standard of UL946A, the CTI of the material is tested and the material is rated according to the results (see the table below).

[0031] Tracking voltage (V) PLC TI≥600 0 400≤TI<600 1 250≤TI<400 2 175≤TI<250 3 100≤TI<175 4 0≤TI<100 5 (4) Precipitation evaluation: The sample is injection molded into a square plate of 100*100*3.0 mm, and aged for 196 h at PCT: 121°C, 2 atmospheres, and 100% humidity. Observe whether there is whitening on the surface of the sample. If whitening occurs, it means that precipitation is obvious and the requirements cannot be met.

[0032] (5) Dimensional stability: The material is injection molded into a 150*30*2mm square plate, and its initial size is tested. The dimensional change in the length direction is evaluated after conditioning in a double 85 degree heat and humidity aging chamber for 48 hours.

[0033] Table 1: PPE / PA alloy distribution ratios (parts by weight) and test results for each group in Examples 1-8 Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Example 8 PPE 40 32 20 17.8 15 25 15 25 PA66 40 48 60 62.2 45 75 PA612 45 PA6T / 66 75 Zinc borate 11 11 11 11 9 15 9 15 Toughener A-1 6 6 6 6 3 12 3 12 Antioxidants 0.5 0.5 0.5 0.5 0.5 0.5 0.5 0.5 Flame retardant V-0 V-0 V-0 V-0 V-0 V-0 V-0 V-0 Low temperature ball drop performance OK OK OK OK OK OK OK OK CTI PLC 0 PLC 0 PLC 0 PLC 0 PLC 0 PLC 0 PLC 0 PLC 0 Separation No whitening No whitening No whitening No whitening No whitening No whitening No whitening No whitening Dimensional change (%) 1.27 1.40 1.53 1.59 1.39 1.43 1.52 1.59 It can be seen from Examples 1-4 and Comparative Examples 1-2 that the dimensional stability decreases with the increase of the nylon content; however, when the PPE content in Comparative Example 1 is too high, the low-temperature ball drop performance is poor and the CTI cannot meet the 0 level; when the nylon content in Comparative Example 2 is too high, the dimensional stability is too poor and the V-0 flame retardant grade cannot be achieved.

[0034] Table 2: Distribution ratios (parts by weight) of each group of PPE / PA alloys in Examples 9-14 and test results Example 9 Example 10 Embodiment 11 Example 12 Embodiment 13 Embodiment 14 PPE 32 32 32 32 32 32 PA66 48 48 48 48 48 48 Zinc borate 7.3 9.1 7.3 9.1 7.3 7.3 Hexaphenoxycyclotriphosphazene 3.7 1.9 3.7 Phenoxy polyphosphazene 3.7 antimony white 3.7 1.9 Toughener A-1 6 6 6 6 6 Toughener B 6 Antioxidants 0.5 0.5 0.5 0.5 0.5 0.5 Flame retardant V-0 V-0 V-0 V-0 V-0 V-0 Low temperature ball drop performance OK OK OK OK OK OK CTI PLC 0 PLC 0 PLC 0 PLC 0 PLC 0 PLC 0 Separation No whitening No whitening No whitening No whitening No whitening No whitening Dimensional change (%) 1.48 1.47 1.46 1.46 1.56 1.58 It can be seen from Examples 2 / 9-13 that the flame retardant is preferably zinc borate, in which case the dimensional stability of the alloy is better.

[0035] It can be seen from Examples 9 / 13 that the dimensional stability is better when the phosphazene is selected from hexaphenoxycyclotriphosphazene.

[0036] Table 3: Distribution ratios (parts by weight) of each group of PPE / PA alloys in Examples 15-17 and test results Embodiment 15 Example 16 Embodiment 17 PPE 32 32 32 PA66 48 48 48 Zinc borate 11 11 11 Toughener A-2 6 Toughener A-3 6 Toughener A-4 6 Antioxidants 0.5 0.5 0.5 Flame retardant V-0 V-0 V-0 Low temperature ball drop performance OK OK OK CTI PLC 0 PLC 0 PLC 0 Separation No whitening No whitening No whitening Dimensional change (%) 1.28 1.31 1.46 It can be seen from Examples 2 / 15 / 16 / 17 that when the maleic anhydride grafting rate of the toughening agent is preferably 0.4-0.7wt%, the dimensional change rate is lower.

[0037] Table 4: Comparative Examples 1-7 PPE / PA alloy distribution ratios (parts by weight) and test results Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 PPE 48 16 32 32 32 32 32 PA66 32 64 48 48 48 48 18 Zinc borate 11 11 7.3 6 25 11 Diethylaluminum hypophosphite 11 3.7 Toughener A-1 6 6 6 6 6 6 1 Antioxidants 0.5 0.5 0.5 0.5 0.5 0.5 0.5 Flame retardant V-0 V-2 V-1 V-0 V-1 V-0 V-0 Low temperature ball drop performance NG OK OK OK OK NG NG CTI PLC 1 PLC 0 PLC 0 PLC0 PLC 0 PLC 0 PLC 0 Separation No whitening No whitening White White No whitening No whitening No whitening Dimensional change (%) 1.15 1.88 1.59 1.57 1.48 1.37 1.36 It can be seen from Comparative Example 3 that the diethyl aluminum hypophosphite flame retardant cannot achieve V-0 flame retardancy in the technical solution of the present invention and is easily precipitated.

[0038] It can be seen from Comparative Example 4 that when the ratio of zinc borate to diethylaluminum hypophosphite is not within an appropriate range, the flame retardant formed will be prone to whitening and have a large dimensional change rate.

[0039] It can be seen from Comparative Example 5 that if the content of the flame retardant of the present invention is insufficient, the flame retardancy level cannot reach V-0.

[0040] It can be seen from Comparative Example 6 that if the content of the flame retardant of the present invention is too high, the low-temperature ball drop performance is poor.

[0041] It can be seen from Comparative Example 7 that if the toughening agent content is too low, the low-temperature ball drop performance is poor.

[0042] Table 5: Comparative Examples 8-14 PPE / PA alloy distribution ratios (parts by weight) and test results Comparative Example 8 Comparative Example 9 Comparative Example 10 Comparative Example 11 Comparative Example 12 Comparative Example 13 Comparative Example 14 PPE 32 32 32 32 32 32 32 PA66 48 48 48 48 48 48 48 Zinc borate 11 5.5 5.5 11 11 11 11 Hexaphenoxycyclotriphosphazene 5.5 antimony white 5.5 Toughener A-1 20 6 6 Toughener A-5 6 Toughener C 6 Toughener D 6 Toughener E 6 Antioxidants 0.5 0.5 0.5 0.5 0.5 0.5 0.5 Flame retardant V-2 V-1 V-2 V-0 V-0 V-0 V-0 Low temperature ball drop performance OK OK OK NG NG NG NG CTI PLC 0 PLC 0 PLC 0 PLC 0 PLC 0 PLC 0 PLC 0 Separation No whitening No whitening No whitening No whitening No whitening No whitening No whitening Dimensional change (%) 1.51 1.50 1.49 1.48 1.69 1.62 1.49 It can be seen from Comparative Example 7 that if the toughening agent content is too low, the low-temperature ball drop performance is poor.

[0043] It can be seen from Comparative Example 8 that if the toughening agent content is too high, the flame retardancy cannot reach V-0.

[0044] It can be seen from Comparative Examples 9-10 that if zinc borate is compounded with other flame retardants, the content of zinc borate cannot be too low, otherwise the flame retardancy will not reach V-0.

[0045] It can be seen from Comparative Examples 11-13 that when GMA is grafted to SEBS, SEBS, and POE, the low-temperature ball drop performance is poor, especially when SEBS and POE are used, the dimensional change rate is high.

[0046] It can be seen from Comparative Example 14 that when the maleic anhydride grafting rate in the maleic anhydride grafted SEBS is 1.5 wt %, the low-temperature ball drop performance is deteriorated.

Claims

1. A halogen-free flame-retardant PPE / PA alloy, characterized in that: By weight, it includes the following components: Polyphenylene ether and polyamide 60-100 parts; 9-15 parts of halogen-free flame retardant; 3-12 parts of toughening agent; The halogen-free flame retardant is selected from at least one of zinc borate, zinc borate / phosphazene compound flame retardant, and zinc borate / antimony white compound flame retardant, wherein the weight ratio of zinc borate / phosphazene is (8-2):1, and the compounding ratio of zinc borate / antimony white is (8-2):1; Wherein, the weight ratio of polyphenylene ether to polyamide is in the range of 1:(1-3.5); The toughening agent is selected from any one or more of maleic anhydride grafted styrene block copolymers and maleic anhydride grafted ethylene-octene copolymers, wherein the grafting rate of maleic anhydride is 0.2-1wt%.

2. The halogen-free flame-retardant PPE / PA alloy according to claim 1, characterized in that: The polyphenylene ether is polymerized from 2,6-dimethylphenol or its derivatives.

3. The halogen-free flame-retardant PPE / PA alloy according to claim 1, characterized in that: The polyamide is selected from at least one of aliphatic polyamide and semi-aromatic polyamide.

4. The halogen-free flame-retardant PPE / PA alloy according to claim 1, characterized in that: The halogen-free flame retardant is selected from zinc borate.

5. The halogen-free flame-retardant PPE / PA alloy according to claim 1, characterized in that: The grafting rate of maleic anhydride in the toughening agent is 0.4-0.7wt%.

6. The halogen-free flame-retardant PPE / PA alloy according to claim 1, characterized in that: The maleic anhydride grafted styrene block copolymer is selected from at least one of maleic anhydride grafted styrene-butadiene-styrene block copolymer, maleic anhydride grafted styrene-ethylene / butylene-styrene block copolymer and maleic anhydride grafted styrene-ethylene / propylene-styrene block copolymer.

7. The halogen-free flame-retardant PPE / PA alloy according to claim 1, characterized in that: The phosphazene is selected from at least one of hexaphenoxy cyclotriphosphazene, phenoxy polyphosphazene, derivatives of hexaphenoxy cyclotriphosphazene, and derivatives of phenoxy polyphosphazene; preferably, the phosphazene is selected from hexaphenoxy cyclotriphosphazene.

8. The halogen-free flame-retardant PPE / PA alloy according to claim 1, characterized in that: The invention also comprises 0.1-2 parts of antioxidant by weight, wherein the antioxidant is selected from at least one of phenolic antioxidant, phosphite antioxidant or metal passivator.

9. The method for preparing the halogen-free flame-retardant PPE / PA alloy according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: mixing the components uniformly according to the proportion, extruding and granulating the components through a twin-screw extruder, wherein the screw speed is 250-500 rpm, and the extrusion temperature is 230-290° C., so as to obtain a halogen-free flame-retardant PPE / PA alloy.

10. The use of the halogen-free flame-retardant PPE / PA alloy according to any one of claims 1 to 8, characterized in that: Used to prepare photovoltaic connectors.

Citation Information

Patent Citations

  • A high heat-resistant halogen-free flame-retardant nylon 6 and its preparation method and application

    CN103865256B

  • High-toughness halogen-free flame-retardant PA66 material and preparation method thereof

    CN115260754A

  • Carbon fiber reinforced polyamide composition, preparation method and application

    CN115873401A